2016
DOI: 10.1103/physrevb.93.140402
|View full text |Cite
|
Sign up to set email alerts
|

Ferrimagnetic ordering and spin entropy of field-dependent intermediate spins inNa0.82CoO2

Abstract: The peculiar field-dependent magnetism of N a0.82CoO2 has been investigated through an analysis of its DC and AC spin susceptibilities. To account for the easily activated narrow b2g-a1g gap of the crystal field for Co in the cobalt oxide layer, the spin-state transition of Co 3+ (3d 6 ) between the low spin (LS) N a x CoO 2 has been shown to have an intriguing and rich electronic phase diagram as a function of Na ions that are sandwiched between CoO 2 layers, including a superconducting state for x∼ 1/3 aft… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, for temperatures well below T N , the localized spins due to oxygen vacancies are distributed randomly and at the excited state, which are expected to order at a temperature much lower than T N . In particular, the isolated spins near the oxygen vacancy sites are expected to be aligned by the local FM environment of the Cu 2+ spins in 1D and 2D (see figure 9), so that the total FM moment per ab-layer does not cancel out along the c-direction completely, similar to the ferrimagnetic ordering for the intermediate spins of Co 3+ which are built on the matrix of the A-type AF ordered Co 4+ spins below T N in Na 0.82 CoO 2 [32]. We have estimated that the spontaneous FM magnetization at 2 K for δ∼0.16 of ∼20 emu mol -1 (inset of figure 8) corresponds to about ∼0.1 μ B per oxygen, which agrees very well with the 0.11 μ B estimated from neutron diffraction study [6].…”
Section: Emergent Fm Moment At Low Temperaturementioning
confidence: 99%
“…On the other hand, for temperatures well below T N , the localized spins due to oxygen vacancies are distributed randomly and at the excited state, which are expected to order at a temperature much lower than T N . In particular, the isolated spins near the oxygen vacancy sites are expected to be aligned by the local FM environment of the Cu 2+ spins in 1D and 2D (see figure 9), so that the total FM moment per ab-layer does not cancel out along the c-direction completely, similar to the ferrimagnetic ordering for the intermediate spins of Co 3+ which are built on the matrix of the A-type AF ordered Co 4+ spins below T N in Na 0.82 CoO 2 [32]. We have estimated that the spontaneous FM magnetization at 2 K for δ∼0.16 of ∼20 emu mol -1 (inset of figure 8) corresponds to about ∼0.1 μ B per oxygen, which agrees very well with the 0.11 μ B estimated from neutron diffraction study [6].…”
Section: Emergent Fm Moment At Low Temperaturementioning
confidence: 99%
“…The layered transition metal oxides have received special attention in condensed matter physics research because of their rich physical properties, including ion intercalation for potential battery applications, superconductivity, and intercalant-sensitive magnetic phase transitions. [1][2][3][5][6][7][8][9][10] The group IA ions that are sandwiched between the transition metal oxide layers act as passive charge reservoirs to influence the electronic structure. P 2-type Na 2 Ni 2 TeO 6 has been shown to exhibit high ionic conductivity at room temperature for potential applications as a separator in the Na-ion battery.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray diffraction studies have shown that the crystal structure of Na 2 Ni 2 TeO 6 can be indexed with a space group P 6 3 /mcm satisfactorily, and a 3D antiferromagnetic (AFM) spin ordering of T N ∼27 K has been proposed; however, the impact of Na ion diffusion on the crystal and spin structure has never been explored in detail, in contrast to its sister compound Na x CoO 2 which has been studied extensively and shown rich physical insights. [3][4][5][6][7][8][9]12,14 It is highly desirable to investigate the 2D structure of the Na-layer that reflects the potential field generated by the (Te/Ni)-O honeycomb sublattice and its relationship to the magnetic structure of Ni spins. In particular, due to the diffusive nature of intercalated Na ions, a unique dynamic magneto-phonon coupling of the system could be revealed through the detailed analysis of the Na ion distribution and crystal structure change as a function of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Since Li has a high electron affinity, making the occurrence of electron sharing with its neighboring oxygen unlikely, a molecular model of the implied interchain exchange coupling through the Cu-O-Li-O-Cu super-superexchange route for Li CuO 2 2 is purely imaginary, though it is often assumed as that depicted in figure 1 of Lorenz 2009, where the ionic bond of the electron donation has extended to σ-bond-type electron sharing for the electron/spin exchange interaction. Similar chemical bond models for the chain and layered compounds, such as Na CoO x 2 and TiSe 2 have been proposed before [18,19], as also noted by Rosner et al regarding the intimate relationship between crystal chemistry and magnetism [20]. Although the MDD interaction is relatively weak compared to that of the spin exchange interaction [17], it becomes non-negligible once the dimension is taken into consideration, which is similar to the character of the van der Waals force of the electric dipole interaction between large areas of layers for most van der Waals materials.…”
Section: J-j′-mentioning
confidence: 53%